1,3-Dipolar cycloaddition reaction of D-glucose-derived nitrone with allyl alcohol: synthesis of 2-hydroxy-1-deoxycastanospermine analogues - Karanjule, Narayan S.; Markad, Shankar D.; Sharma, T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2005)
The synthesis and evaluation of glycosidase inhibitory activity of polyhydroxylated indolizidine alkaloids namely 2-hydroxy-1-deoxycastanospermine 3a,b and 2-hydroxy-1-deoxy-8a-epi-castanospermine 3c,d is reported. The key step involves the intermolecular 1,3-dipolar cycloaddition of allyl alcohol to D-glucose-derived nitrone 4, followed by tosylation, that afforded four diastereomeric sugar-substituted isoxazolidines 5a-d with the desired regioselectivity. The one-pot conversion of 5a-d to pyrrolidines 8a-d by hydrogenolysis, removal of 1,2-acetonoide functionality, and hydrogenation afforded corresponding target molecules 3a-d.

Aziridine carboxylate from D-glucose: synthesis of polyhydroxylated piperidine, pyrrolidine alkaloids and study of their glycosidase inhibition - Dhavale, Dilip D.; Kumar, K. S. A.; Chaudhari, Vinod D.; Sharma, T.; Sabharwal, Sushma G.; PrakashaReddy, J. (Organic & Biomolecular Chemistry, 2005)
The D-glucose derived aziridine carboxylate 5 was obtained from (E)-ethyl-6-bromo-1,2-O-isopropylidene-3-O-benzyl-5-deoxy-alpha-D-xylo-5 -eno-heptofuranuronate 4 through conjugate addition of benzylamine and in situ intramolecular nucleophilic expulsion of bromine. The regioselective aziridine ring-opening, using water as a nucleophile, resulted in the alpha-hydroxy-beta-aminoester 6, which was exploited in the synthesis of six and five membered azasugars 1b/1c and 2b/2c, respectively The glycosidase inhibitory activity of the title compounds was evaluated.

Bicyclic amino acid-carbohydrate-conjugates as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres - Kale, Sangram S.; Chavan, Sanjay T.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Sanjayan, Gangadhar J. (Organic & Biomolecular Chemistry, 2011)
This communication describes a general synthetic route to bicyclic amino acid-carbohydrate-conjugates, which would be useful as conformationally restricted hydroxyethylamine (HEA) transition-state isosteres. The synthesis was achieved in 12 steps starting from D-glucose. The striking features of this system are the bicyclic rigid core displaying an a-amino acid side chain and hydroxyethylamine moiety - both of which would be potentially important for receptor interactions, leading to various biomedical responses, as described in the literature. Crystal structure investigation suggested extensive intermolecular hydrogen-bonding interactions in this system, involving the backbone amide and hydroxyl groups.

Alpha-geminal dihydroxymethyl piperidine and pyrrolidine iminosugars: synthesis, conformational analysis, glycosidase inhibitory activity, and molecular docking studies - Pawar, Nitin J.; Parihar, Vijay Singh; Chavan, Sanjay T.; Joshi, Rakesh S.; Joshi, Pranaya V.; Sabharwal, Sushma G.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2012)
The Jocic-Reeve and Corey-Link type reaction of dichloromethyllithium with suitably protected 5-keto-hexofuranoses followed by treatment with sodium azide and sodium borohydride reduction gave 5-azido-5-hydroxylmethyl substituted hexofuranoses 7a-c with required geminal dihydroxymethyl group. Removal of protecting groups and converting the C-1 anomeric carbon into free hemiacetal followed by intramolecular reductive aminocyclization with in situ generated C5-amino functionality afforded corresponding 5C-dihydroxymethyl piperidine iminosugars 2a-c. Alternatively, removal of protecting groups in 7b and 7c and chopping of C1-anomeric carbon gave C2-aldehyde that on intramolecular reductive aminocyclization with CS-amino gave 4C-dihydroxyrnethyl pyrrolidine iminosugars 1b and 1c, respectively. On the basis of the H-1 NMR studies, the conformations of 2a/2b were assigned as C-4(1) and that of 2c as C-1(4). The glycosidase inhibitory activities of all five iminosugars were studied with various glycosidase enzymes and compared with natural o-g/uco-l-deoxynojirimycin (DNJ). All the five compounds were found to be potent inhibitors of rice alpha-glucosidase with K-i and IC50 values in the nanomolar concentration range. Iminosugars 2b and 1b were found to be more potent inhibitors than their parent iminosugar. These results were substantiated by in silico molecular docking studies.

Green synthesis of polysaccharide stabilized gold nanoparticles: chemo catalytic and room temperature operable vapor sensing application - Tagad, Chandrakant K.; Rajdeo, Kishor S.; Kulkarni, Atul; More, Pooja; Aiyer, Rohini C.; Sabharwal, Sushma G. (RSC Advances, 2014)
A facile, one pot, completely green, and cheap route for the synthesis of gold nanoparticles (AuNPs) has been developed by using locust bean gum (LBG), both as a reducing and a stabilizing agent. Synthesized AuNPs were characterized by UV-vis spectroscopy, TEM, XRD, dynamic light scattering analysis (DLS) and EDAX. A characteristic surface plasmon peak at 537 nm confirmed the formation of AuNPs. Synthesized AuNPs were found to be an efficient catalyst for the reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP). The reaction follows pseudo-first order kinetics with a rate constant of 14.46 X 10(-2) min(-1). Furthermore, the catalytic efficiency of AuNPs for ethanol vapor sensing was investigated by doping AuNPs in a tin oxide (SnO2) matrix synthesized by a single step thermal decomposition method. The AuNPs doped SnO2 sensor showed a fast response (similar to 5 seconds) and excellent ethanol sensing behavior in the range of 10 to 120 ppm at room temperature. A two fold increase in ethanol vapor sensing response was observed with AuNPs doped SnO2 as compared with the pure SnO2 sensor.

Lannea coromandelica attenuates glucagon and oxyntomodulin mediated cAMP formation in HEK cells stably-expressing human glucagon receptor - Walunj, Sameer; Gupta, Rajesh; Joshi, Swati P.; Sabharwal, Sushma G.; Joshi, Kalpana (Journal of Herbal Medicine, 2015)
Antagonism of glucagon is a potential therapeutic approach for Type 2 diabetes mellitus (T2DM). The bark extract of Lannea coromandelica has been reported to have hypoglycemic or anti-diabetic effects on animal models and human subjects. The aim of this study was to elucidate the molecular mechanisms of L. coromandelica extract as a glucagon receptor antagonist. The aqueous extract of L. coromandelica bark attenuated glucagon-mediated cAMP formation in a concentration dependent manner with an IC50 value of 4.24 +/- 1.31 mu g/ml. It shifted a concentration response curve of glucagon towards the right with a 4, 21 and 40-fold change in IC50 at 6.25, 12.5 and 25 mu g/ml of extract, respectively. Additionally, it attenuated an oxyntomodulin-mediated cAMP response. The extract was found specifically to inhibit glucagon mediated cAMP formation since it was ineffective in reducing cAMP levels nonspecifically-elevated by forskolin. The data support that the aqueous extract of L. coromandelica antagonizes the glucagon receptor and has the potential to reduce glucagon mediated liver glucose output. (C) 2015 Elsevier GmbH. All rights reserved.
Keywords: cAMP; Diabetes; Glucagon; Lannea coromandelica; Mechanism; Oxyntomodulin